'A collective commitment to improving cooperation on migration': analysis of a thematic consultation session for the Global Compact for Migration. Issue 9 (29th July 2022) - van Riemsdijk, Micheline; Panizzon, Marion
Abstract: The adoption of the New York Declaration in 2016 launched a two-year process to create a Global Compact for Safe, Orderly and Regular Migration (GCM), starting with an intergovernmental (informal) thematic consultation phase involving non-governmental actors. This article presents a framing analysis of preparatory materials and video recordings of stakeholder interventions for a thematic session on international cooperation and governance of migration. It examines the involvement of non-governmental actors in the GCM policymaking process and the opportunities and challenges in international cooperation on migration. The findings show that member states' concerns about national sovereignty, uncertainty about the consultation process, and varied framings of certain policy-issue areas presented considerable obstacles to international cooperation. At the same time, the open-ended outcome of the consultations phase enabled non-governmental actors to move discussions beyond state sovereignty and border control. We argue that the participation of non-governmental actors in consultation sessions broadened the bargaining table with 'softer type' issues, while the breadth of topics levelled out the playing field of international cooperation.